SISTEM INFORMASI AKADEMIK BERBASIS WEB PADA SMK YPI-ALFALAH JAKARTA TIMUR - Syahbaniar Rofiah; Tuty Haryanti (Jurnal Sistem Informasi, 2014)
Abstract -- Making a website about academic information system is one way to develop the existing school management system, with the system, schools can inform and manage the value of the good. So with the website of the academic information systems students, teachers, and visitors can find information about the schools directly. Schools can also process data and student grades quickly, effectively and efficiently. Academic information system contained in vocational schools YPI-Alfalah in entering data (input), change, and display data (output) reported only gets direct administration resulting in inaccurate reports as well as teachers and students must come to school to get information about value or data required. Such information system is less effective in the management of the school, in order to provide convenience both to inform students and teachers needed liveliness management system.